Mind the gaps: a qualitative study of perceptions of healthcare professionals on challenges and proposed remedies for cervical cancer help-seeking in post conflict northern Uganda - Mwaka, Amos D.; Wabinga, Henry R.; Mayanja-Kizza, Harriet (BMC family practice, 2013)
There are limited data on perceptions of health professionals on challenges faced by cervical cancer patients seeking healthcare in the developing countries. We explored the views of operational level health professionals on perceived barriers to cervical screening and early help–seeking for symptomatic cervical cancer and the proposed remedies to the challenges.Fifteen key informant interviews were held with health professionals including medical directors, gynecologists, medical officers, nurses and midwives in the gynecology and obstetrics departments of two hospitals in northern Uganda during August 2012 to April 2013. We used content analysis techniques to analyze the data.Health professionals’ perceived barriers to cervical cancer care included: (i) patients and community related barriers e.g. lack of awareness on cervical cancer and available services, discomfort with exposure of women’s genitals and perceived pain during pelvic examinations, and men’s lack of emotional support to women (ii) individual healthcare professional’s challenges e.g. inadequate knowledge and skills about cervical cancer management; (iii) health facility related barriers e.g. long distances and lack of transport to cervical cancer screening and care centers, few gynecologists and lack of pathologists, delayed histology results, lack of established palliative care services and inadequate pain control; and (iv) health policy challenges e.g. lack of specialized cancer treatment services, and lack of vaccination for human papilloma virus. Other challenges included increased number of cervical cancer patients and late stage of cervical cancer at presentations.Operational level healthcare professionals in northern Uganda reported several practical challenges facing cervical cancer care that influence their decisions, management goals and practices. The challenges and proposed remedies can inform targeted interventions for early detection, management, and control of cervical cancer in Uganda.
Keywords: Barriers to care, Cervical cancer, Northern Uganda, Healthcare professionals